An empirical comparison of atypical bulimia nervosa and binge eating disorder - Leonardo F. Fontenelle; Mauro V. Mendlowicz; Rodrigo O. Moreira; José Carlos Appolinário (2005)
The International Classification of Diseases, 10th edition (ICD-10) defines atypical bulimia nervosa (ABN) as an eating disorder that encompasses several different syndromes, including the DSM-IV binge eating disorder (BED). We investigated whether patients with BED can be differentiated clinically from patients with ABN who do not meet criteria for BED. Fifty-three obese patients were examined using the Structured Clinical Interview for DSM-IV and the ICD-10 criteria for eating disorders. All volunteers completed the Binge Eating Scale (BES), the Beck Depression Inventory, and the Symptom Checklist-90 (SCL-90). Individuals fulfilling criteria for both ABN and BED (N = 18), ABN without BED (N = 16), and obese controls (N = 19) were compared and contrasted. Patients with ABN and BED and patients with ABN without BED displayed similar levels of binge eating severity according to the BES (31.05 ± 7.7 and 30.05 ± 5.5, respectively), which were significantly higher than those found in the obese controls (18.32 ± 8.7; P < 0.001 and P < 0.001, respectively). When compared to patients with ABN and BED, patients with ABN without BED showed increased lifetime rates of agoraphobia (P = 0.02) and increased scores in the somatization (1.97 ± 0.85 vs 1.02 ± 0.68; P = 0.001), obsessive-compulsive (2.10 ± 1.03 vs 1.22 ± 0.88; P = 0.01), anxiety (1.70 ± 0.82 vs 1.02 ± 0.72; P = 0.02), anger (1.41 ± 1.03 vs 0.59 ± 0.54; P = 0.005) and psychoticism (1.49 ± 0.93 vs 0.75 ± 0.55; P = 0.01) dimensions of the SCL-90. The BED construct may represent a subgroup of ABN with less comorbities and associated symptoms.